Efisiensi Pengunaan Media Kartu Kata Bergambar dalam Meningkatkan Kemampuan Membaca Permulaan pada Anak Tunagrahita Ringan di SLB Negeri Manekat Niki-Niki - Poletika, Florentinus; Wangge, Vinsensius; Selan, Ot Bill Wilson; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2025)
Initial reading is crucial in the learning process, as it is a basic skill every student must possess to progress to advanced reading. Students who lack initial reading skills will struggle to understand various learning materials in class. In reality, many students still lack initial reading skills appropriate to their age. Researchers even found that students in a class as a whole had difficulty with initial reading. The purpose of this study was to determine the difficulties experienced by students in learning initial reading, to identify the factors causing these difficulties, and to determine how teachers address these difficulties so that the learning objectives are optimally achieved. This study used the Classroom Action Research (CAR) method. Data collection techniques used observation sheets, interviews, and document analysis. Participants in this study were three ninth-grade students at the Manekat Niki-Niki State Special Needs School. The results showed that three students in the class had difficulty learning initial reading into syllables, and students had difficulty spelling syllables into words. This difficulty is caused by three factors: physical factors, interest factors, and family factors. Therefore, teachers make efforts to overcome these students' early reading difficulties by inviting students to spell letters while singing, reminding students of the benefits and importance of reading, and contacting parents/guardians to pay more attention to students' reading activities at home.